2017
DOI: 10.1186/s12943-017-0727-3
|View full text |Cite
|
Sign up to set email alerts
|

Linc-RoR promotes MAPK/ERK signaling and confers estrogen-independent growth of breast cancer

Abstract: BackgroundThe conversion from estrogen-dependent to estrogen-independent state of ER+ breast cancer cells is the key step to promote resistance to endocrine therapies. Although the crucial role of MAPK/ERK signaling pathway in estrogen-independent breast cancer cell growth is well established, the underlying mechanism is not fully understood.MethodsIn this study, we profiled lncRNA expression against a focused group of lncRNAs selected from lncRNA database. CRISPR/Cas9 was employed to knockout (KO) linc-RoR in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
130
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 182 publications
(131 citation statements)
references
References 49 publications
1
130
0
Order By: Relevance
“…In our study, we found that CoCl 2 inactivated ERK while activated MAPK pathways while ROR overexpression reversed this trend shown by activation of ERK and inactivation of MAPK. Our study was consistent with the previous study that lncRNA ROR activated ERK pathway through in breast cancer [33]. Our study went further and unveiled one possible underlying in which miR-145 was involved in.…”
Section: Discussionsupporting
confidence: 92%
“…In our study, we found that CoCl 2 inactivated ERK while activated MAPK pathways while ROR overexpression reversed this trend shown by activation of ERK and inactivation of MAPK. Our study was consistent with the previous study that lncRNA ROR activated ERK pathway through in breast cancer [33]. Our study went further and unveiled one possible underlying in which miR-145 was involved in.…”
Section: Discussionsupporting
confidence: 92%
“…Besides, it both inhibits p53 translation [42] and enhances c-Myc expression through interaction with heterogeneous nuclear ribonucleoprotein I (hnRNP I) [43]. While in triple negative breast cancer, linc-RoR increases cell invasion via miR-145/ ARF6 pathway [44], in estrogen receptor positive breast tumors it activates MAPK/ ERK pathway through diminish ing the stability of dual specificity phosphatase 7 (DUSP7) which down-regulates ERK [45].…”
Section: Lincrna Regulator Of Reprogramm Ing (Linc-ror)mentioning
confidence: 99%
“…linc-ROR is important in regulating epithelial-to-mesenchymal transition (EMT) and can promote breast cancer progression and metastasis through the regulation of miR-NAs (Hou et al, 2014). linc-ROR also functions as an onco-lncRNA to promote the estrogen-independent growth of ER-positive breast cancer and to contribute to tamoxifen resistance (Peng et al, 2017). linc-ROR is an important marker for multidrug resistance in breast cancer, and its upregulation is important for chemotherapy tolerance (Chen et al, 2016a), and it confers the resistance of breast cancer cells to gemcitabine by silencing miR-34a expression (Chen et al, 2016b).…”
Section: Introductionmentioning
confidence: 99%